Tissue phosphoproteomics with PolyMAC identifies potential therapeutic targets in a transgenic mouse model of HER2 positive breast cancer. Issue 24 (12th June 2014) - Searleman, Adam C.; Iliuk, Anton B.; Collier, Timothy S.; Chodosh, Lewis A.; Tao, W. Andy; Bose, Ron; Nilsson, Carol; Lichti, Cheryl; Liu, Huiling
<x xml:space="preserve">Abstract</x> Altered protein phosphorylation is a feature of many human cancers that can be targeted therapeutically. Phosphopeptide enrichment is a critical step for maximizing the depth of phosphoproteome coverage by MS, but remains challenging for tissue specimens because of their high complexity. We describe the first analysis of a tissue phosphoproteome using polymer‐based metal ion affinity capture (PolyMAC), a nanopolymer that has excellent yield and specificity for phosphopeptide enrichment, on a transgenic mouse model of HER2‐driven breast cancer. By combining phosphotyrosine immunoprecipitation with PolyMAC, 411 unique peptides with 139 phosphotyrosine, 45 phosphoserine, and 29 phosphothreonine sites were identified from five LC‐MS/MS runs. Combining reverse phase liquid chromatography fractionation at pH 8.0 with PolyMAC identified 1571 unique peptides with 1279 phosphoserine, 213 phosphothreonine, and 21 phosphotyrosine sites from eight LC‐MS/MS runs. Linear motif analysis indicated that many of the phosphosites correspond to well‐known phosphorylation motifs. Analysis of the tyrosine phosphoproteome with the Drug Gene Interaction database uncovered a network of potential therapeutic targets centered on Src family kinases with inhibitors that are either FDA‐approved or in clinical development. These results demonstrate that PolyMAC is well suited for phosphoproteomic analysis of tissue specimens.